Mongolia : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2005 Article IV Consultation highlights that Mongolia's overall economic performance was stronger than expected and broad based in 2004 and early 2005. Sectoral contributions to high growth included a rebound in the livestock sector from harsh winter shocks of 2000-01 and strong mining exploration and exports, boosted by a favorable environment of unusually high copper and gold prices. After several years of moderation, however, inflation has accelerated, reaching 17 1\2 percent through June 2005, as prices of fuels and meat have increased sharply in the past twelve months.